PENGEMBANGAN DAYA TARIK DAN POTENSI WISATA AIR TERJUN LOKOQ SEKOAH DI KABUPATEN LOMBOK UTARA - Yahadi Yahadi; Lalu Masyhudi; Lalu Mohamad Iswadi Athar (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
This study examines the development of the attraction and tourism potential of the Lokoq Sekoah Waterfall in North Lombok Regency. This study aims to determine the development of what potentials the Lokoq Sekoah Waterfall Tourism Destination has and what problems are encountered in developing the Lokoq Sekoah Waterfall Tourism Destination. This research is a qualitative descriptive study with data collection techniques, namely observation, interviews and documentation. The results of this study indicate that the tourist attraction of Lokoq Sekoah Waterfall is very potential to be developed in North Lombok Regency. In the development of the Lokoq Sekoah Waterfall Tourism Destination, it turns out that there are still various obstacles, including the lack of supporting facilities and infrastructure so that in the future it really requires support from the community, managers, private sector and North Lombok Regency Government.